PENDEKATAN RISK MANAGEMENT & ANALISIS SWOT UNTUK MENGANTISIPASI PENURUNAN LABA DI ECOS MINIMART GRESIK - hari bahari; Eko Budi Leksono; Elly Ismiyah (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2018)
Retail industry in Indonesia is growing rapidly and cause a very tight competition. Competition in the retail business by the nature of the retail business which is very difficult to differentiate, so many retail businesses are closed. Understanding the scope of the retail business means understanding management related to finance, marketing, and operational resources. Including the risks to be faced. Then there should be a risk management against targets retail market. Risk management is basically a series of processes are performed to minimize the level of risk to the acceptable range. In this research, risk management approach and SWOT analysis to anticipate the decline in retail profit. The purpose of risk management is to establish the context of risk, risk identification, risk analysis, risk evaluation and risk treatment. Failure mode effect analysis (FMEA) is one application of risk management to measure severity, occurance and detection. From the results of severity, occurance and detection calculated risk priority number (RPN) to do the elimination of the cause of the risk based on the highest RPN. Furthermore, the risk with the highest RPN do risk treatment recomendation.Risk treatment could be strength based on the internal and external aspects by integrating with SWOT analysis. The results of SWOT analysis integration into FMEA is used to determine the appropriate risk treatment measures based on the preference score. Based on risk management approach and SWOT analysis its can be recomended risk treatment produced with preference value score that is greater than the risk of treatment initial conditions. At the risk of shortage of operational costs for credit limit smelting employee cooperative members (KKS). Treatment of the initial condition is to limit the risk of a credit limit in accordance with the conditions Ecos Minimart with score 1.39 preference value, whereas the recomended risk treatment is to change the credit limit system into a system of deposit to the value of the preference score of 1.45, as well as other risk treatment.